Evaluation of Disease Stage and Severity in Depression Patients with MOXO Continuous Performance Test - Ozgur Aytas; Kursat Sahin Yildirimer; Irem Yasar Aytas (Britain International for Academic Research (BIAR) Publisher, 2025)
Studies have shown significant impairments in cognitive functions in patients with major depressive disorder. This study aims to measure the loss of ability in sub-parameters of cognitive functions that occurs with changes in the severity of depression, using objective methods. In the study, the application of the computer-based neuropsychological test MOXO d-CPT to patients diagnosed with depression and the relationship between the sub-parameters obtained from this test, such as attention, timing, impulsivity, and hyperactivity, and the stage and severity of depression were examined. The study included 225 adult participants aged 18-65, who were admitted to a psychiatric clinic between 2022 and 2024 and diagnosed with Major Depression according to DSM-V diagnostic criteria. Beck Depression Inventory was administered to each participant, the MOXO d-CPT Performance Test was conducted, and a socio-demographic data form was filled out. The aim of the study is to reveal the correlation between depression severity and cognitive impairments and to provide a detailed characterization of impairments in the subcomponents of executive functions. The effects of this study on cognitive processes in relation to depression severity are expected to contribute to the literature by revealing impairments in attention, timing, impulsivity, and hyperactivity parameters at different stages of depression with objective data.